Magnetic resonance cholangiopancreatography: practical experience in 30 subjects - Nurman, A (Faculty of Medicine, Trisakti University, 2008)
Magnetic resonance cholangiopancreatography (MRCP) is a noninvasive method of imaging the biliary and pancreatic ducts. No special patient preparation is required but the usual contraindications to MR scanning apply. The diagnostic performance of MRCP in most biliary tract diseases is similar to that of more invasive techniques of direct cholangiography such as endoscopic retrograde cholangiopancreatography (ERCP). The objectives of this study were to investigate the diagnostic efficacy of MRCP in patients with abdominal pain with lesser likelihood of having choledochal stone and to determine whether use of MRCP could eliminate the need for purely diagnostic endoscopic retrograde cholangio-pancreatography (ERCP). A total of 30 patients with suspected biliopancreatic pathology from several hospital was studied retrospectiely between January 2007 and December 2008 in Jakarta. The sensitivity and specificity of MRCP was 92.59% (95% Confidence Interval, 74.25 - 98.71%) and 66.67% (95% Confidence Interval, 12.53 – 98.23%), respectively. The positive predictive value of MRCP for all biliary pathology was 96.15% (95% Confidence Interval, 78.42 – 99.79%) The negative predictive value of MRCP was 50.00% (95% Confidence Interval, 9.19 – 90.81%). MRCP seems to be effective in diagnosing patients with abdominal pain with lesser likelihood of having choledochal stone.